The Political Economy of Labor Market Regulation with R&D - Tapio K. Palokangas (Institute for the Study of Labor (IZA), 2014)
In this paper, I study the political rationale for labor market regulation. Oligopolists employ raw labor and human capital (i.e. key workers) for production and R&D. There are many jurisdictions, in each of which a self-interested policy maker can regulate/deregulate the local labor market. I show that the observed tendency to labor market deregulation results from labor market policies being set up at the local level. In small jurisdictions, the fall of income due to wage increases is so large that the labor markets are deregulated. With labor market integration, jurisdictions get larger and face less competition from outside. Then, the fall of income due to wage increases is reduced and labor market regulation becomes more attractive to workers' lobbies.
Keywords: F15; J50; O40; 330; political economy; labour market regulation; R&D; union power